Pergeseran Peran Mahkamah Konstitusi dalam Menangani Pelanggaran Pemilihan Umum TSM: Analisis Hukum dan Konstitusional - Muh Farhan Arfandy; A Rafika Maharani (Adagium: Jurnal Ilmiah Hukum, 2026)
This article examines the Constitutional Court’s authority in adjudicating structured, systematic, and massive (TSM) electoral violations in Indonesia’s 2019 and 2024 presidential elections. Using a normative legal and comparative approach, it evaluates the Court’s application of the judicial restraint principle and its limitations when violations do not quantitatively affect election results but may undermine electoral legitimacy. Findings reveal that the Court consistently rejects examining TSM allegations without evidence of direct impact on vote counts. However, in cases involving ethical and constitutional violations, this approach may fall short in ensuring substantive electoral justice. A comparative study with five other countries shows that several constitutional courts have adopted a more progressive role in safeguarding the integrity of the electoral process. The article recommends strengthening constitutional interpretation and reforming the legal framework to enable Indonesia’s Constitutional Court to act as a guardian of both electoral outcomes and democratic fairness.